Citizen Scientists Are Not Just Quiz Takers: Information about Project Type Influences Data Disclosure in Online Psychological Surveys. (28th January 2022) - Rudnicka, Anna; Gould, Sandy; Cox, Anna
Traditionally, citizen science has centred on giving lay people opportunities to learn about science by participating in it. Lately, psychological citizen science projects have increasingly aimed to attract participants by providing an opportunity for self-learning. Unfortunately, these citizen science projects sometimes resemble quizzes hosted by private companies that have been criticised for suboptimal privacy practices. We were interested in whether similarity to these dubious quizzes could jeopardise the ability of citizen science projects to collect sensitive personal data. We found that people who join an online quiz disclose a lower volume of sensitive data than those who join a citizen science project. Moreover, post-recruitment encouragement to learn about science influenced data disclosure among quiz takers but not among citizen scientists. These findings have implications not only for the effective design of citizen science but also for the broader debate about consent to disclose data in research, academic or otherwise.